Editorial: Beyond the food systems framework: food system transitions toward sustainable healthy diets in low and middle-income countries - Berg, Marrit van den; Lecoutere, Els; Termote, Céline; Hunter, Danny (Frontiers Media, 2022)
Food systems are failing to deliver sufficient, healthy and affordable food. Poor diets are a leading contributor to the global burden of disease while malnutrition is among the leading causes of death (Afshin et al., 2019). The high cost of healthy diets coupled with persistent high levels of income inequality put healthy diets out of reach for around three billion people throughout the world (FAO, 2021). The sustainability of how we produce, distribute and consume food is of increasing concern. Further, the COVID-19 pandemic has demonstrated crises can cause significant disruptions to food systems (Carducci et al., 2021). Reshaping how we produce and consume food ensuring human and planetary health is a key global challenge highlighted by recent and ongoing UN dialogues through the Food Systems Summit, Climate Change Conference (COP26) and forthcoming Biodiversity Conference (COP15).